Некоторые замечания о лексике перевода “Лекарства на оспалый умыслъ чоловьчъй” (Острог, 1607) - Еренбург, М. (Kalbotyra, 1974)
A collection under the title contains three works of confessional literature. They all are written in Church Slavonic and Old Ukrainian. Data exists about the translator.Thus there is no necessity to make primary textual investigation; the degree of reliable generalization increases; comparison with works about which there is no special information (author, date, place of creation) becomes possible.The paper presents a description of one of the possible ways of comparison of the two languages in the collection; it defines the reasons and conditions of functioning of words in the translation which are different in origin (Church Slavonic, Polish and Old Ukrainian).Such a comparison gave the possibility to determine the fact that this vocabular variety was caused by the necessity of reflecting the semantics and figurativeness of the words in the original and by the possibilities of the language of the translation.